Development of Wordwall-Based Educational Mathematics Game Learning Media for Statistics Material - Fitri Yanti; Andinasari Andinasari; Risda Intan Sistyawati (Program Studi Pendidikan Matematika, 2025)
Mathematics learning, particularly in statistics topics, still faces the problem of low student learning motivation, which is influenced by the use of less varied instructional strategies. This study aims to develop a Wordwall-based educational mathematics game as a learning medium for statistics that is valid, practical, and allows observation of its impact on students’ learning motivation. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were tenth-grade students of SMA Sjakhyakirti, with a field trial conducted in class X.3 involving 37 students. Data collection methods included questionnaires and interviews. The data were analyzed using descriptive quantitative techniques. The results showed that the developed media had a very high level of validity, with percentages of 90.66% from media experts and 93.75% from subject matter experts. Student responses indicated a practicality level of 97.11%, categorized as very practical. In addition, the percentage of students’ learning motivation reached 97.08%, categorized as very high. Therefore, the Wordwall-based educational mathematics game media is feasible to be used as an alternative learning medium to enhance students’ learning motivation in statistics at the senior high school.